Validating the Data Completeness and Accuracy of the Canadian Cystic Fibrosis Registry - Ranjani Somayaji; Stephanie Y. Cheng; Noma Abdulrahem; Sanja Stanojevic; Paul Eckford; Bradley S. Quon; Elizabeth Cromwell; Albert Faro; Christopher H. Goss; Anne L. Stephenson (Canadian Respiratory Journal)
Conclusion: Our validation of the CCFR demonstrated high accuracy for clinical and demographic variables used in clinical research.